Modificação de filmes de gelatina por adição de surfactantes e ácidos graxos de coco e sua aplicação na conservação de melão Charentais sob refrigeração - Ferreira, Rafaella Martins de Araújo (Universidade Federal Rural do Semi-Árido, 2012)
The development of edible films for application in food industry, as a substitute for traditional plastic films is an emphasis on research. In view of the need to evaluate the characteristics of water vapor permeability of gelatin films to improve its efficiency in postharvest conservation of fruits, this study had aim to promote modification of gelatin films by addition of surfactants and coconut fatty acids and their subsequent application in the conservation of Charentais melon under refrigeration. The study of the effect of addition of coconut fatty acids and of two surfactants (coconut oil saponified and Tween 20) in gelatin films was carried out using an experimental design to centroid simplex type mixtures. According with the response variables (permeability to water vapor and transmittance at 550 nm) it was verified that the composition with better characteristics for use on fruit (low permeability to water vapor and high transparency) was the gelatin film and 5% coconut oil saponified. In the following experiment was used the completely randomized design in a split plot with the treatments in the plot (control, LDPE film and biofilm) and subplot in factorial scheme 5 x 2, with five periods of storage at 5 º C (7, 10, 13, 16 and 19 days) and two periods of shelf life at 20 ° C (zero and three days). The following characteristics were evaluated: mass loss, internal and external appearance, pulp firmness, soluble solids, pH, titratable acidity, vitamin C and total soluble sugars. It was verified during the storage, increase in mass loss and decrease in the following characteristics: notes of internal and external appearance, in titratable acidity, soluble solids, total soluble sugars and in the content of vitamin C. It was noted that the LDPE film was more effective in retarding the mass loss of the fruits while the biofilm was effective in prolonging the fruits firmness
Modification of gelatin films by addition of surfactants and coconut fatty acids and their application in the preservation of Charentais melon under refrigeration
Keywords: Cucumis melo L.; Storage; Biofilm; Gelatin; Cucumis melo L.; Armazenamento; Biofilme; Gelatina; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA